Training of public activists, public sportsmen and mass sports referees from students (Eurasian Journal of Humanities and Social Sciences, 2022)
The process of training of public activists on Physical Culture and sports - public sportsmen and judges of mass sports for selection methods and their training was expressed from the students.It is intended for future specialists in the field of Physical Culture and sports – bachelors and Masters and teachers of the subject of multi-disciplinary physical education